SpoIIIE mechanism of directional translocation involves target search coupled to sequence‐dependent motor stimulation. (5th April 2013) - Cattoni, Diego I; Chara, Osvaldo; Godefroy, Cédric; Margeat, Emmanuel; Trigueros, Sonia; Milhiet, Pierre‐Emmanuel; Nöllmann, Marcelo
Abstract : SpoIIIE/FtsK are membrane‐anchored, ATP‐fuelled, directional motors responsible for chromosomal segregation in bacteria. Directionality in these motors is governed by interactions between specialized sequence‐recognition modules (SpoIIIE‐γ/FtsK‐γ) and highly skewed chromosomal sequences (SRS/KOPS). Using a new combination of ensemble and single‐molecule methods, we dissect the series of steps required for SRS localization and motor activation. First, we demonstrate that SpoIIIE/DNA association kinetics are sequence independent, with binding specificity being uniquely determined by dissociation. Next, we show by single‐molecule and modelling methods that hexameric SpoIIIE binds DNA non‐specifically and finds SRS by an ATP‐independent target search mechanism, with ensuing oligomerization and binding of SpoIIIE‐γ to SRS triggering motor stimulation. Finally, we propose a new model that provides an entirely new interpretation of previous observations for the origin of SRS/KOPS‐directed translocation by SpoIIIE/FtsK. SpoIIIE mechanism of directional translocation involves target search coupled to sequence‐dependent motor stimulation: SpoIIIE is an ATP‐dependent motor required for chromosome segregation in bacteria. This study shows that pre‐formed hexameric SpoIIIE associates non‐specifically with DNA and finds specific sequences (SRS) by ATP‐independent target search. The interaction with SRS then triggers SpoIIIE motor stimulation.